Resenhas - Cláudia Pereira de Almeida, Ana; Weiss Costa, Gregory; Cardoso Brum, Janaina; Contreras, Matilde; Caetano, Veridiana; Marchioro Stumpf, Elisa; Carboni Garcia, Simone (Revista Linguagem & Ensino, 2019)
Esta seção contém resenhas de sete livros.